DAMPAK KEBIJAKAN REACH (REGISTRATION, EVALUATION, AUTHORIZATION AND RESTRICTION CHEMICALS) UNI EROPA TERHADAP EKSPOR TEKSTIL INDONESIA TAHUN 2007-2012 - Leni, Suriani; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of this research is explains the impactment of REACH (registration, evaluation, authorization, and restriction chemicals) as a European Union’s regulation to export textile’s product of Indonesia. This research describes about the impact of REACH that created by ECHA (European Chemicals Agency) to improve protection of human health and the environment from the risks of chemicals. This research applies qualitative research method. The author collects data from books, encyclopedia, academic journals, mass media and sources from the internet that discuss about REACH and the impact to export of Indonesia textile’s product. This research use nation state analysis, liberalism perspective, and mercantilism theory. The conclusion is the impactment of REACH is failed export textile product and the decrease export textile’s product of Indonesia.Keywords: Chemicals, ECHA, REACH, Textile and Textile’s product